An exploratory study on teenagers' view on sex education syllabus before receiving formal sex education lesson in school / Asmidar Lokman, Farah Adilla Abd Rahman and Shamsinar Rahman - Lokman, Asmidar; Abd Rahman, Farah Adilla; Rahman, Shamsinar (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The constant baby dumping issue reported in the news has raised major concerns among all Malaysians. The National Registration Department reported that there were over 155,700 young Muslim mothers, including those who are still in school gave birth to babies out of wedlock between 2000 and 2008 (The Star, 7th December 2010). Hence, the public has demanded the government to take action in order to curb this appalling occurrence from taking place again. Some suggested finding out the root cause of the problem. Tuan Guru Nik Aziz Nik Mat, Kelantan Menteri Besar opined that sex education in schools would encourage teenage sexual promiscuity. He insisted that the best way to resolve this issue is to instill greater Islamic values in our children at an early age. Tun Dr. Mahathir Muhammad commented that sex education in schools was unnecessary because students are already getting Islamic and moral education. Much of the upheaval, the government decided to introduce sex education in school as a long-term strategy in dealing with this particular social problem. The subject known as the Social and Reproductive Health Education module will be introduced to primary and secondary school children starting from January 2011. The idea is to introduce sex education early before the children reach puberty so that they have time to decide for themselves on matters of sexuality and sex. This research-based paper aims to find out the level of knowledge the teenagers on sex and sexuality and their perception on the content of the syllabus before they receive formal sex education lessons in class.